1986
DOI: 10.1084/jem.163.3.665
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal elastase and cathepsin G in beige mice. Neutrophils of beige (Chediak-Higashi) mice selectively lack lysosomal elastase and cathepsin G.

Abstract: A profound decrease in activities of the two lysosomal serine proteinases, elastase, and cathepsin G, was found in neutrophils of four independent beige mutants. Elastase and cathepsin G activities were assayed with the specific synthetic substrates MeO-Suc-Ala-Ala-Pro-Val-MCA and Suc-Ala-Ala-Pro-Phe-pNA, respectively. The defect is intrinsic to cells of beige mice, since transplantation of bone marrow from normal to mutant mice restored normal proteinase activity, and normal mice transplanted with beige marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 40 publications
3
52
1
Order By: Relevance
“…2). More recent studies in beige mnice, using specific enzymatic substrates, determined that both elastase and cathepsin t enzymatic activities were deficient (13). In this study, we observed the same type of dual deficiency in human CHS PMN, and were able to show by Western blotting for elastase and cathepsin G that the enzymatic deficiency paralleled a deficiency of the respective immunoreactive proteins.…”
Section: Resultssupporting
confidence: 64%
“…2). More recent studies in beige mnice, using specific enzymatic substrates, determined that both elastase and cathepsin t enzymatic activities were deficient (13). In this study, we observed the same type of dual deficiency in human CHS PMN, and were able to show by Western blotting for elastase and cathepsin G that the enzymatic deficiency paralleled a deficiency of the respective immunoreactive proteins.…”
Section: Resultssupporting
confidence: 64%
“…As reviewed by Weissmann et a1 (12), C5a will not only stimulate chemotaxis, but will also induce inflammatory cells to release proinflammatory mediators and degradative enzymes. The resistance seen in B6 beige mice may reflect this dual role of C5a, since neutrophils in these mice are not only chemotactically defective (7), but degradative enzymes, cathepsin G and elastase, are absent (13).…”
Section: Discussionmentioning
confidence: 99%
“…To compare WT and ⌬␣ M PMN degranulation in response to C. albicans, the level of intracellular ␤-glucuronidase retained in PMNs granules upon activation was determined by modification of described methods (57,93). C. albicans ( 10 7 ) of either CAI-12 or ⌬Pra1 strains were allowed to germinate overnight in 1 ml of RPMI 1640 medium; 10 6 peritoneal or peripheral blood PMNs, either WT or ⌬␣ M derived, were then added in 0.5 ml of HBSS-HEPES (pH 7.4) containing 2 mM CaCl 2 and 2 mM MgCl 2 , followed by incubation at 37°C in 5% CO 2 for 30 min.…”
Section: Methodsmentioning
confidence: 99%